2017
DOI: 10.1016/j.msksp.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualising manual therapy skills in contemporary practice

Abstract: With conflicting evidence regarding the effectiveness of manual therapy calls have arisen within some quarters of the physiotherapy profession challenging the continued use of manual skills for assessment and treatment. A reconceptualisation of the importance of manual examination findings is put forward, based upon a contemporary understanding of pain science, rather than considering these skills only in terms of how they should "guide" manual therapy interventions. The place for manual examination findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…Through critical self-reflection on biomechanical theories and models which are thought be be central to an osteopathic approach, [39,40], practitioners should appraise the value and plausibility of their dominant approaches and practice paradigms that guide their clinical work as well as to better reconceptualise and expand the rationale of the therapeutic effects of the osteopathic manipulative treatment (OMT) in patients with musculoskeletal related chronic pain [29,60]. This would enable the development of more person-centered framework, that may help osteopaths to enhance their confidence and competence in the identification of obstacles to healing, outside the "joint" [30,47].…”
Section: Implications For Osteopathymentioning
confidence: 99%
“…Through critical self-reflection on biomechanical theories and models which are thought be be central to an osteopathic approach, [39,40], practitioners should appraise the value and plausibility of their dominant approaches and practice paradigms that guide their clinical work as well as to better reconceptualise and expand the rationale of the therapeutic effects of the osteopathic manipulative treatment (OMT) in patients with musculoskeletal related chronic pain [29,60]. This would enable the development of more person-centered framework, that may help osteopaths to enhance their confidence and competence in the identification of obstacles to healing, outside the "joint" [30,47].…”
Section: Implications For Osteopathymentioning
confidence: 99%
“…Cervical mobilisations -low velocity passive oscillatory movements 3 , are frequently used to treat neck pain 4,5 , but their effectiveness has been questioned by recent systematic reviews [6][7][8] . The heterogeneity of participants in randomised controlled trials (RCT) has been suggested as an explanation for the lack of positive findings as an effect in a subgroup of patients may be diluted by the absence of an effect in others 9,10 . Evidence suggests that treatment outcomes with cervical mobilisations are improved when their application is based on patient subclassification [11][12][13] .…”
mentioning
confidence: 99%
“…Palpation is an inherent and basic skill of health professionals, particularly manual therapists who base their diagnosis and treatment in a clinical environment [1]. Thus, palpation abilities are still critical in physical testing [2,3].…”
Section: Introductionmentioning
confidence: 99%